Intra-breath arterial oxygen oscillations detected by a fast oxygen sensor in an animal model of acute respiratory distress syndrome - Formenti, F; Chen, R; McPeak, H; Murison, P J; Matejovic, M; Hahn, C E W; Farmery, A D (British journal of anaesthesia, 2015)
BACKGROUND: There is considerable interest in oxygen partial pressure (Po2) monitoring in physiology, and in tracking Po2 changes dynamically when it varies rapidly. For example, arterial Po2 ([Formula: see text]) can vary within the respiratory cycle in cyclical atelectasis (CA), where [Formula: see text] is thought to increase and decrease during inspiration and expiration, respectively. A sensor that detects these [Formula: see text] oscillations could become a useful diagnostic tool of CA during acute respiratory distress syndrome (ARDS). METHODS: We developed a fibreoptic Po2 sensor (<200 µm diameter), suitable for human use, that has a fast response time, and can measure Po2 continuously in blood. By altering the inspired fraction of oxygen ([Formula: see text]) from 21 to 100% in four healthy animal models, we determined the linearity of the sensor's signal over a wide range of [Formula: see text] values in vivo. We also hypothesized that the sensor could measure rapid intra-breath [Formula: see text] oscillations in a large animal model of ARDS. RESULTS: In the healthy animal models, [Formula: see text] responses to changes in [Formula: see text] were in agreement with conventional intermittent blood-gas analysis (n=39) for a wide range of [Formula: see text] values, from 10 to 73 kPa. In the animal lavage model of CA, the sensor detected [Formula: see text] oscillations, also at clinically relevant [Formula: see text] levels close to 9 kPa. CONCLUSIONS: We conclude that these fibreoptic [Formula: see text] sensors have the potential to become a diagnostic tool for CA in ARDS.
Keywords: technologie optických vláken; Fiber Optic Technology; Animals; Respiratory Distress Syndrome; Female; acute respiratory distress syndrome; zvířata; arterial oxygen monitoring; cyclical atelectasis; fibreoptic sensor; modely nemocí na zvířatech; prasata; syndrom dechové tísně; Oxygen; Swine; kyslík; ženské pohlaví; Disease Models, Animal